Advance Organizer dalam Pembelajaran Sosiologi Bermakna - Abdurrachim Setiawan; Atik Catur Budiati (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
This study examines the implementation of the advance organizer strategy in fostering meaningful learning in sociology and identifies the challenges encountered by teachers during its implementation. The research was motivated by the need to strengthen students' conceptual understanding by connecting prior knowledge with newly acquired concepts through structured instructional strategies. A descriptive qualitative approach employing a case study design was adopted. The participants comprised sociology teachers and students from Classes X.E1 and X.E11 at State Senior High School 3 Surakarta during the 2025/2026 academic year. Data were collected through non-participant observation, in-depth interviews, and documentation of lesson planning and classroom activities. The findings indicate that the advance organizer strategy was implemented through four principal practices: structured introductory activities grounded in authentic social phenomena, flexible use of instructional media such as videos, images, and news articles, integration of prior and new knowledge through pop quizzes and guided questioning, and reinforcement of key concepts during lesson closure. Nevertheless, its implementation was constrained by limited student participation, heterogeneous prior knowledge, less conducive classroom conditions, and inadequate supporting facilities. The study concludes that advance organizer strategies can effectively promote meaningful sociology learning when complemented by initial diagnostic assessment and instructional scaffolding that align with students' cognitive structures.